A promised land - Obama, Barack (Crown, 2020)
Obama tells the story of his improbable odyssey from young man searching for his identity to leader of the free world, describing in strikingly personal detail both his political education and the landmark moments of the first term of his historic presidency--a time of dramatic transformation and turmoil.